2006
DOI: 10.1007/s10509-005-9025-4
|View full text |Cite
|
Sign up to set email alerts
|

The Red Rain Phenomenon of Kerala and its Possible Extraterrestrial Origin

Abstract: A red rain phenomenon occurred in Kerala, India starting from 25th July 2001, in which the rainwater appeared coloured in various localized places that are spread over a few hundred kilometers in Kerala. Maximum cases were reported during the first 10 days and isolated cases were found to occur for about 2 months. The striking red colouration of the rainwater was found to be due to the suspension of microscopic red particles having the appearance of biological cells. These particles have no similarity with usu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 5 publications
0
15
1
Order By: Relevance
“…Although the nature of the red compounds is still uncertain, it is clear from this investigation that these compounds firmly intercalate deep into the thick outer layers of these cells, which may facilitate resistance to hostile environments. The results presented here do not make the origin of the red rain cells of Kerala any clearer, but do clearly indicate the presence of DNA, and offer an explanation for the negative staining results reported by Louis & Kumar (2006).…”
Section: Extraction Of Red Pigment With Dmso Allows Permeability To Scontrasting
confidence: 78%
See 2 more Smart Citations
“…Although the nature of the red compounds is still uncertain, it is clear from this investigation that these compounds firmly intercalate deep into the thick outer layers of these cells, which may facilitate resistance to hostile environments. The results presented here do not make the origin of the red rain cells of Kerala any clearer, but do clearly indicate the presence of DNA, and offer an explanation for the negative staining results reported by Louis & Kumar (2006).…”
Section: Extraction Of Red Pigment With Dmso Allows Permeability To Scontrasting
confidence: 78%
“…The rain was characterized by red pigmented particles that were initially characterized as Trentepohlia algae, fungal spores, desert sand or even red blood cells, but were shown to have structural features consistent with bacterial spores (Louis & Kumar, 2006). The inability of those authors to detect DNA by conventional staining methods prompted them to suggest that the red rain cells might have an extraterrestrial origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Indian case, the red rain was preceded by a loud sonic boom heard in the sky, the presumption being that an icy meteoroid laden with red rain cells exploded in the stratosphere, and the red cells subsequently seeded tropospheric rain clouds. Despite intensive investigations of both the Kerala and Sri Lankan red rain, their content of red cells still remains unidentified [33,34]. The most plausible explanation remains that the red cells although superficially similar to terrestrial algae are of a totally unidentified genus and species, possible an alien cometary microorganism.…”
Section: Microfossils In Meteoritesmentioning
confidence: 99%
“…In 2002, it was claimed that germs recovered in From 25 July to 23 September 2001, red rain sporadically fell on the southern Indian state of Kerala. In early 2006, these events gained widespread attention when the media reported that two physicists of the Mahatma Gandhi University in Kottayam proposed a controversial hypothesis that the coloured particles were ET cells [14]. In 2008, they announced that the red cells found in the red rain in Kerala, India, are now considered a possible case of an extra-terrestrial life form.…”
Section: (B) the Hungarian Dds-mso Hypothesismentioning
confidence: 99%